The Relevance of Qiyas in Contemporary Legal Determination : Analysis of the Perspective of Usul Fiqh - Halim, Abdul; Muhlizar, Muhlizar (CV. Tripe Konsultan, 2024)
Qiyas is one of the source Islamic law which is of a nature rational and have role important in development Islamic law in particular in answer problem contemporary that is not in a way explicit mentioned in the Qur'an and Hadith. this article aiming For analyze relevance and validity the use of qiyas in determination law to modern issues such as digital transactions reproduction artificial, and development technology financial, through approach principle fiqh. Research This use method qualitative-descriptive with approach normative as well as study literature to works classic and contemporary in field principle fiqh . Results of the analysis show that qiyas remains relevant as instruments of ijtihad in respond dynamics social and contemporary developments during fulfil conditions for valid qiyas according to the scholars. With Thus qiyas does not only functioning as tool complement but also as means important in guard flexibility and sustainability Islamic law in the modern era.